Predictors of Unachieved LDL Levels in Ischemic Stroke Patients Treated with Statins in Yogyakarta Indonesia - Amelia Rumi, Jarir Atthobari, Rizaldy Pinzon, Agung Endro Nugroho (Journal of Applied Pharmaceutical Science, 2014)
Ischemic stroke occurs due to barriers in cerebral vascular. The barriers are manifestation of atherosclerosis formation. Statins are widely used in patients with high level of LDL. The aim of the study was to investigate the factors that influence the Unachieved LDL levels in ischemic stroke patients treated with statin. The study was an analytical research performed using a nested case-control study. The subjects were ischemic stroke patients based on inclusion criteria, and treated with statin. The patients were classified into case group if the result of medical record and the stroke register showed the LDL level of the patients was >100 mg/dL. Whereas the ischemic stroke patients with LDL level
Keywords: Ischemic stroke, predictors, LDL levels.